Three-dimensional realignment and slope reducing osteotomy with anatomic ACL reconstruction in patients with revision anterior cruciate ligament deficiency. Issue 9 (28th September 2020) - Imhoff, Andreas B.; Feucht, Matthias; Achtnich, Andrea; Imhoff, Florian; Herbst, Elmar; Diermeier, Theresa
Introduction: Current incidence of recurrent anterior cruciate ligament (ACL) instability is 5%, but revision surgery is challenging and requires a thorough analysis of potential risk factor. Moreover, recurrent and chronic ACL instability can result in medial tibio-femoral osteoarthritis (OA). Beside various soft tissue patterns, bony morphologies like a steep posterior tibial slope are associated with an increased anterior tibial translation (ATT) and rotatory instability in the ACL deficient knee. To address the instability and the osteoarthritis a combined procedure is necessary in these patients, however, little is known about the efficacy of such combined procedures. Therefore, the objective of this study was to evaluate the patient reported outcomes and knee stability following combined high tibial osteotomy (HTO) with ACL reconstruction in middle-aged patients with recurrent or chronic cruciate ligament deficiency and mild to moderate medial compartment osteoarthritis (OA). Hypotheses: Methods: Surgical reports and prospectively collected patient reported outcome scores (IKDC, Lysholm, WOMAC, VAS for pain, and Tegner activity score) as well as clinical examination were evaluated retrospectively with a mean follow up of 45.2 ± 14.7 months. Inclusion criteria were 1) high tibial osteotomy with concomitant anatomic ACL reconstruction. Data at final followup were compared to baseline values using the Wilcoxon signed rank test (p < 0.05). Results: 44 patients met the inclusion criteria. 16/44 suffered a graft failure after primary ACL reconstruction, and 8/44 had chronic ACL instability, but had a previous subtotal medial meniscus resection. Mean patient age at surgery was 38.2 ± 10.5 years (range: 18 – 63) with a mean varus alignment of 4.5° ± 1.5°. All patient reported significantly improved outcome scores at final follow-up (VAS 4.3 to 1.5, Lysholm 52.4 to 73.5, IKDC 56.5 to 70.9). However, the change in Tegner score at final follow-up (3.4 to 4.5) was not significant. At final followup 25/44 patients had a removal of the fixation plate. Conclusion: The results of this study indicate, that high tibial osteotomy combined with anatomic single bundle ACL reconstruction is a good treatment option in active middle aged patients suffering from recurrent or chronic ACL deficiency with mild to moderate medial compartment OA. At a median follow-up of 24 months patient reported outcome scores were improved. Especially in patients with multiple ACL reconstruction failures realignment osteotomies should be considered.